2014
DOI: 10.1002/ejsp.2074
|View full text |Cite
|
Sign up to set email alerts
|

Different relational models underlie prototypical left and right positions on social issues

Abstract: Social issues are important dividing lines in the “culture wars” between the political left and right. Despite much research into social issue stance and ideology, little research has explored these with Relational Models Theory (RMT). RMT proposes four distinct models that people use to construe social relations, each entailing distinct moral considerations. In two studies, participants read summaries of the models, rated how relevant each was to their positions on several social issues (e.g., capital punishm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 41 publications
1
18
0
1
Order By: Relevance
“…The present findings suggest there is some predictive validity to incorporating Equity and, to a lesser extent, Proportionality, but much work remains to investigate whether including Proportionality or Equity would enhance MFT’s ability to predict other meaningful phenomena such as religious beliefs or altruistic social action. Although we cannot speak to whether our results hold in other cultures, there is reason to believe Proportionality concerns are not particular to the United States (Simpson & Laham, 2015). The Protestant work ethic (PWE, the belief that hard work leads to success) appears in a range of cultures (Furnham et al, 1993) but relates to policy attitudes and prejudice in different ways depending on the culture (Rosenthal, Levy, & Moyer, 2011).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…The present findings suggest there is some predictive validity to incorporating Equity and, to a lesser extent, Proportionality, but much work remains to investigate whether including Proportionality or Equity would enhance MFT’s ability to predict other meaningful phenomena such as religious beliefs or altruistic social action. Although we cannot speak to whether our results hold in other cultures, there is reason to believe Proportionality concerns are not particular to the United States (Simpson & Laham, 2015). The Protestant work ethic (PWE, the belief that hard work leads to success) appears in a range of cultures (Furnham et al, 1993) but relates to policy attitudes and prejudice in different ways depending on the culture (Rosenthal, Levy, & Moyer, 2011).…”
Section: Discussionmentioning
confidence: 75%
“…Little work has explored the utility of Proportionality in distinguishing political partisans, but in one such study, Simpson and Laham (2015) used relational models theory, an alternative framework of moral motives, to predict conservatives’ and liberals’ stances on various social issues. The authors found mixed support for Market Pricing, an equivalent to the concept of Proportionality, in distinguishing conservatives’ and liberals’ positions.…”
Section: Discussionmentioning
confidence: 99%
“…One item was used each for measuring political interest (1 = no interest at all to 5 = high interest) and political orientation (1 = left to 10 = right), while the latter was used to calculate political extremity by coding those at both scale end points as high extremity and the middle point as low extremity. We also assessed participants’ personal moral foundations (based on the Moral Foundations Questionnaire; [ 46 , 47 ]), reaching acceptable reliabilities for individualizing (12 items: Cronbach’s α = .77) and binding foundations (18 items; Cronbach’s α = .84).…”
Section: Studymentioning
confidence: 99%
“…Hence, the very same moral action should be judged differently, depending on the moral motive implicated in the relational context. Beyond substantial empirical validation of RRT's precursor, Relational Models Theory (see Haslam, 2004), RRT itself has received some preliminary empirical support (Simpson & Laham, 2015a, 2015b.…”
mentioning
confidence: 99%